Endovascular stent graft repair of the ascending aorta—final frontier in the endovascular treatment of the aorta - Kubota, Hiroshi (Journal of Thoracic Disease, 2016)
Endovascular aortic/aneurysm repair (EVAR) of the abdominal aorta was performed first, and it was followed by thoracic endovascular aortic/aneurysm repair (TEVAR) for true aneurysm. Aortic arch aneurysms later came to be treated by TEVAR with various debranching techniques. The indications for TEVAR have recently been extended to the treatment of a majority of symptomatic type B aortic dissections with rupture or malperfusion. The indication for uncomplicated type B aortic dissections is controversy; however, large entry size, partially thrombosed false lumen, and larger aortic diameter in acute phase are regarded as risk factors for worse outcome (1-3). Therefore, TEVAR has been proposed as a means to prevent late complications by covering the primary entry tear and obtain the thrombosed remodeled false lumen. Although ascending TEVAR is currently limited to high surgical risk patients with aortic pathologies originating above the sinotubular junction and there is no consensus in regard to a standardized technique, the aortic root and ascending aorta are now the final frontiers for treatment by TEVAR.